Memory and value of syncopation: on the difference between what the old and the modern teach (Per Musi, 2010)
Syncopation is a privileged issue in popular music studies that reappears here in a number of considerations that, marked by the bias of knowledge of the old disciplines of Counterpoint and Harmony, underline the interaction and, especially, the inseparability between metric (division, rhythm, accentuation, prosody, etc.) and pitches (notes, intervals, dissonance-consonance relationship, chords, auxiliary notes, etc.) in a critical analysis of the figures of syncopation. The first part covers up a minimum memory of the art and theory of syncopation in the Western erudite tradition, so that, in the second part, it can be noted that, in tacit and subtle manner, residues of this tradition can affect the value judgment in some of the syncopated worlds of popular music today.